Radical Islam's rules the worldwide spread of extreme Shari'a law - Marshall, Paul A. (Rowman & Littlefield, 2005)
Shows the effects Shari'a law has on human rights, especially the status of women and religious freedom, of Muslims as well as religious minorities and democracy itself. It concludes with policy recommendations for the United States regarding specific countries confronting extreme Shari'a.